Invoking the idealized family to assess political leadership and legitimacy: news coverage of Australian and Canadian premiers. Issue 2 (17th February 2022) - Auer, Meagan; Trimble, Linda; Curtin, Jennifer; Wagner, Angelia; Woodman, V. K. G.
ABSTRACT: Conventional wisdom holds that women politicians confront a parenting dilemma. Those with children are questioned about their ability to balance parental roles with political responsibilities, but child-free women are regarded as unable to relate to "ordinary" families or perform well in "feminine" policy areas. As both women and men are now balancing parenthood with politics, the time is ripe to re-investigate how cultural ideas about family life shape understandings of political leadership. By systematically comparing newspaper coverage of 22 Canadian and Australian government leaders with diverse families, our study investigates the ways in which discourses of family shape representations of high-profile politicians. It provides valuable insights into the ways in which politicians' levels of conformity to the idealized western family model shape perceptions of political legitimacy and authenticity for women and men, and parents and non-parents. We find that when the families of newly elected leaders are discussed in newspaper coverage, the message conveyed is that only the "right" kind of family will facilitate political success.